An in silico and chemical approach towards small protein production and application in phosphoproteomics1. Issue 25 (21st March 2015) - Dias, Ana M. G. C.; Iranzo, Olga; Roque, Ana C. A.
<x xml:space="preserve">Abstract</x> This work demonstrates the advantages of peptide chemical synthesis as a robust method for the production and modification of small proteins, such as the human Pin1 WW domain. The protein was immobilized on a solid support and used to enrich phosphorylated species.